Perceptions of Trust Digital Payments as A Reduction of Corruption and Use of Fake Money on User Satisfaction of Non-Bank (Digital Payment Applications in Kota Pekanbaru) - Halim Dwi Putra; A.Malik; Tengku Kespandiar (International ABEC, 2022)
This research is a research on the use of digital payments in non-bank digital payment applications such asOVO, Gopay and DANA which is viewed from the perspective of users in the city of Pekanbaru. The purpose of thisstudy was to determine the level of public trust and satisfaction with non-bank private applications for digital paymentsin the city of Pekanbaru, to find out the success of the Indonesian government's program in promoting the NationalNon-Cash Movement (GNNT) in the city of Pekanbaru, to determine the level of public understanding of digitalpayments. From non-bank applications in the city of Pekanbaru, Knowing the spread of digital payments in the city ofPekanbaru. GNNT can reduce the use of counterfeit money and OTT Actions (Operation Catch Hands) Theimplementation of hand arrest operations (OTT) is one of the strategies used by the Corruption EradicationCommission (KPK) to crack down on corruption cases in Indonesia. The contribution of this research to thedevelopment of the marketing concept of digital payments made by non-bank publishers who allegedly received publictrust in using the National Non-Cash Movement (GNNT) to succeed even though it is not from a bank whose data baseof incoming and outgoing money can be tracked digitally. The results of the research carried out are through the resultsof data analysis using linear regression analysis it can be seen that Perceived Value and Trust have an effect onConsumer Satisfaction, where the effect is significant. The results of the analysis show that the effect is partiallyPerceived Value (X1) on Consumer Satisfaction (Y1) is 0.263 or 26.3%, and the effect is partially Trust (X2) onConsumer Satisfaction (Y1) is 0.246 or 24.6%, thus the hypothesis which states that Perceived Value and Trust havea significant effect on Consumer Satisfaction proven or acceptable. This research is in line with the research beforewhich states that Perceived Value and Trust has a positive relationship with Customer Satisfaction. This result is alsosupported which states that the perception of quality, and, trust, through commitment affect customer loyalty whichpreviously met customer satisfaction.